A relational perspective on public sector leadership and management. Issue 1 (4th February 2014) - Clark, Michael; Denham-Vaughan, Sally; Chidiac, Marie-Anne
Abstract : Purpose: – The purpose of this paper is to discuss critical perspectives on what has become a dominant approach to public sector management and leadership in England and sets out a new conceptual perspective on leadership to improve this situation, namely a relational one. Design/methodology/approach: – A review of key literature on the topics discussed. Findings: – A new relational perspective on leadership and management is proposed, along with epistemological, ethical and practical considerations. Research limitations/implications: – The paper proposes this new approach to leadership and management in the public sector, but no empirical findings are discussed. Practical implications: – The perspective proposes that an explicit consideration of relationships and contextual factors should lie at the heart of leadership and management and all its practice. Originality/value: – This is the first time that a relational perspective on public sector management and leadership has been explicated.